Myositis and acute kidney injury in bacterial atypical pneumonia: Systematic literature review. Issue 12 (December 2020) - Simoni, Chiara; Camozzi, Pietro; Faré, Pietro B.; Bianchetti, Mario G.; Kottanattu, Lisa; Lava, Sebastiano A.G.; Milani, Gregorio P.
Abstract: Background: Bacterial community-acquired atypical pneumonia is sometimes complicated by a myositis or by a renal parenchymal disease. Available reviews do not mention the concurrent occurrence of both myositis and acute kidney injury. Methods: In order to characterize the link between bacterial community-acquired atypical pneumonia and both myositis and a renal parenchymal disease, we reviewed the literature (United States National Library of Medicine and Excerpta Medica databases). Results: We identified 42 previously healthy subjects (35 males and 7 females aged from 2 to 76, median 42 years) with a bacterial atypical pneumonia associated both with myositis (muscle pain and creatine kinase ≥5 times the upper limit of normal) and acute kidney injury (increase in creatinine to ≥1.5 times baseline or increase by ≥27 μmol/L above the upper limit of normal). Thirty-six cases were caused by Legionella species (N = 27) and by Mycoplasma pneumoniae (N = 9). Further germs accounted for the remaining 6 cases. The vast majority of cases (N = 36) presented a diffuse myalgia. Only a minority of cases (N = 3) were affected by a calf myositis. The diagnosis of rhabdomyolysis-associated kidney injury was retained in 37 and that of acute interstitial nephritis in the remaining 5 cases. Conclusion: Bacterial atypical pneumonia may occasionally induce myositis and secondary kidney damage.